Preparedness for Mandatory CSR Reporting of Multinational Companies: Case of the Czech Republic - Renata Skýpalová; Hana Bohušová; Milan Křápek (Ital Publication, 2024)
The way how multinational corporations integrate CSR activities into their business practices and communicate them to stakeholders can significantly impact their market position and business reputation. This paper evaluates the perceived level of preparedness for non-financial reporting associated with social, environmental, and economic CSR activities in selected multinational corporations operating in the Czech Republic. A questionnaire survey for this research was conducted between September 2021 and January 2022, targeting a specific group of multinational corporations established in EU countries and operating in the Czech Republic. As non-financial reporting is expected to be extended to a considerably large number of companies in the near future, this research has high practical relevance for stakeholders involved in decision-making processes. It is valuable for academics as well as the findings revealed statistically significant differences in the understanding of the degree of preparedness for non-financial reporting on individual CSR activities among the respondents. Doi: 10.28991/ESJ-2024-08-03-013 Full Text: PDF